The Shaping of the Economic Area in the State-Building Framework: Eastern El Salvador, 1840-1855 - Pérez Fabregat, Clara (Revista Complutense de Historia de América, 2012)
From the dissolution of the Central American federation until the middle of 19th century, the Eastern region of El Salvador enjoyed a privileged economic position because of its proximity of the port of La Union, on the Bay of Fonseca, a commercial enclave that supported the entire region of San Miguel, which was traditionally interrelated with Southern Honduras and Western Nicaragua. The economic development of San Miguel was the main economic driving force in the initial period of state-formation in El Salvador. This article attempts to explain the project that facilitated the configuration of the regional economy and, at the same time, generated the resources that gave shape to a new political entity.